THE CONCEPT OF TABAYYŪN IN THE QUR’ĀN: EFFORTS TO ADDRESS THE SPREAD OF INFORMATION ON SOCIAL MEDIA - Purnama, Rizal Faturohman (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2021)
This research discusses the discourse of the concept of tabayyūn contained in the Qur'ān as an effort to address the dissemination of information on social media. This research is included in qualitative study models as well as using thematic interpretation views using descriptive-analytical methods that will be contextualized with today's phenomenon. This research comes down to the findings, namely that discursus tabayyun in the Qur’ān is one way to verify the dissemination of information to find a valid source of information. Contextualization of the understanding of the concept of tabayyūn, requires scholars who are experts in their fields to speak to clarify information that is considered troubling to society with the support of the power of the ruler in a country. This brings up the efforts of tabayyūn concept on social media by collaborating with various models of information literacy in accordance with existing conditions, in order to create harmonious communication in the middle of people's lives.